Shape memory polyimide material with biomimetic super-hydrophobic function and preparation method thereof
Patent Information
- Application Number
- CN202611213538.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]为了解决形状记忆聚酰亚胺材料因吸水导致性能下降,在潮湿环境下长期稳定性与可靠性不足的问题,本发明提供了一种仿生超疏水功能的形状记忆聚酰亚胺材料及其制备方法
[0017](1)本发明选用氨基丙基庚基-笼型倍半硅氧烷(POSS)作为功能改性组分,该POSS分子外侧修饰的氨基官能团能够在与形状记忆聚酰亚胺共混过程中发生反应,以共价键方式实现在聚酰亚胺分子链末端的封端,从而将其稳定锚定于聚酰亚胺网络中,有效提升两相相容性;同时,其外侧接枝的庚基链作为一种较长链烷基,属于典型的低表面能化学基团,可在材料表面形成疏水层,降低其与水分子之间的相互作用力,增强材料的整体疏水性能。
Smart Images

Figure CN122958699A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a superhydrophobic polymer film and its preparation method, specifically to a biomimetic superhydrophobic shape memory polyimide material and its preparation method. Background Technology
[0002] Shape memory polyimides (SMPIs) are a class of special engineering materials with unique intelligent responsiveness among high-temperature polymers. They combine the excellent thermal stability, mechanical strength, and chemical stability of polyimides, and possess the ability to recover from a temporary shape to its initial memory shape under external stimuli (such as temperature, light, and electric fields). These properties make them promising for applications in aerospace, microelectronics, and biomedicine. However, polyimide materials exhibit hydrophilic properties due to the polar imide rings in their main chain, which to some extent limits their long-term stability and reliability in humid, highly corrosive, or easily polluted environments. Therefore, surface functionalization modification of SMPIs, especially the construction of superhydrophobic surfaces, has become an important approach to improve their environmental adaptability and functional integration.
[0003] Superhydrophobic surfaces (SHS) are advanced functional interfaces with extreme water repellency, defined as having a contact angle greater than 150° and a roll-off angle less than 5°. This characteristic primarily stems from their rough surface structure, which effectively traps air and forms a stable air cushion layer, thereby significantly reducing the actual contact area between water droplets and the solid surface. On this surface, water droplets exhibit a near-perfect spherical shape, contacting the surface with only a tiny contact point, making them highly susceptible to rolling off under external forces. Furthermore, based on this fundamental principle, superhydrophobic surfaces show broad application prospects in areas such as anti-icing, fluid drag reduction, corrosion resistance, and microfluidic control.
[0004] Currently, in terms of chemical structure modification, existing technologies for hydrophobic modification of polyimide materials can effectively reduce the adsorption sites of hydrophilic polar groups on water molecules by introducing fluorine-containing groups, silicon-containing groups, or flexible segments, thereby reducing the water absorption rate of the material. In particular, in recent years, polyhedral oligomeric silsesquioxanes (POSS) with nanoscale organic-inorganic hybrid cage structures have become a research hotspot. POSS molecules themselves have low surface energy characteristics, and when blended with polymers, they can induce the formation of stable nanoscale protrusions on the polymer surface, synergistically reducing surface energy and constructing necessary micro-nano roughness, which can effectively reduce the hydrophilicity of the material. In terms of physical structure control, nanoscale and micron-scale composite rough structures can be synergistically constructed on the polyimide surface through biomimetic template methods, electrospinning, laser etching, and other technologies. This maximizes air trapping and increases the contact angle of water droplets while reducing their roll-off angle, thereby significantly improving the hydrophobic properties of the material.
[0005] In summary, the hydrophilicity of the imide ring in the polyimide molecule affects the reliability of the material in extreme environments, making it difficult to achieve long-term stable service under aerospace, extreme chemical, and other conditions. Therefore, designing a superhydrophobic functional surface with strong bonding and good stability on polyimide materials has become a key research focus and technical challenge. Summary of the Invention
[0006] To address the performance degradation caused by water absorption and the lack of long-term stability and reliability in humid environments in shape memory polyimide materials, this invention provides a biomimetic superhydrophobic shape memory polyimide material and its preparation method. The method first introduces low surface energy POSS at the molecular level, and then covalently capsulates the ends of the polyimide molecular chains with its reactive functional groups, thereby chemically enhancing the material's inherent hydrophobicity. Furthermore, a self-made polymer template is used to precisely replicate the micron- and nano-composite rough structure of a lotus leaf surface, constructing a similar biomimetic micro / nano morphology on the material surface. This morphology effectively traps air to form an air cushion layer, significantly increasing the water contact angle and reducing the roll-off angle, achieving stable and durable superhydrophobic properties in the shape memory polyimide material.
[0007] The objective of this invention is achieved through the following technical solution:
[0008] A biomimetic superhydrophobic shape memory polyimide material is a fluorinated polyimide end-capped with cage-like silsesquioxane (POSS). The main structure is copolymerized from 4,4'-(hexafluoroisopropene)phthalic anhydride (6FDA) and 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane (HFBAPP) in a molar ratio of 1.05:1.
[0009] A method for preparing the above-mentioned biomimetic superhydrophobic shape memory polyimide material includes the following steps:
[0010] Step S1: Mix PDMS elastomer matrix and curing agent in a weight ratio of 10:1 to obtain PDMS prepolymer; fix a fresh lotus leaf with veins removed at the bottom of the molding mold, pour the PDMS prepolymer into the mold, and place it in an oven at 60~80℃ for 3~5 hours to cure; after curing, separate the PDMS from the mold and use it as a biomimetic template.
[0011] Step S2: Dissolve HFBAPP in DMAc solvent, add 6FDA to the HFBAPP solution in 4-6 portions, react at room temperature under N2 atmosphere for 20-30 h to obtain a polyamic acid solution, named PAA; the solid content of the polyamic acid solution is 10-30 wt%.
[0012] Step S3: Pour PAA onto a glass plate and place it in a vacuum oven for vacuum drying to remove air bubbles, resulting in PAA that is free of air bubbles after curing. The vacuum drying process is as follows: heat to 40~60℃ and hold for 1~3 hours, then heat to 80~100℃ and hold for 1~3 hours.
[0013] Step S4: Place the cured PAA (without bubbles) in a high-temperature oven and perform thermal imidization by gradient heating to obtain a polyimide (PI) film. The gradient heating process is as follows: heat to 110-130℃ at a heating rate of 1-5℃ / min, hold for 1-3 hours; heat to 150-170℃ at a heating rate of 1-5℃ / min, hold for 1-3 hours; heat to 190-210℃ at a heating rate of 1-5℃ / min, hold for 1-3 hours; heat to 240-260℃ at a heating rate of 1-5℃ / min, hold for 1-3 hours; heat to 290-310℃ at a heating rate of 1-5℃ / min, hold for 1-3 hours.
[0014] Step S5: Cut the PI film into small pieces and add it to DMAc solvent. Under N2 atmosphere, stir for 10-15 hours until dissolved. Add NH2-POSS to the solution and react at room temperature for 10-15 hours under N2 atmosphere to obtain a POSS-terminated PI solution, named POSS-PI. The concentration of NH2-POSS in the POSS-terminated PI solution is 2-10 wt%. The PI film dissolves in DMAc with a solid content of 5-15 wt%.
[0015] Step S6: Pour the POSS-PI solution onto the PDMS template, place it in a vacuum oven at 80~100℃ for 1~3 hours, remove air bubbles, cure, demold, and obtain a shape memory polyimide material with biomimetic superhydrophobic function.
[0016] Compared with the prior art, the present invention has the following advantages:
[0017] (1) In this invention, aminopropylheptyl-cage silsesquioxane (POSS) is selected as the functional modification component. The amino functional group modified on the outside of the POSS molecule can react with shape memory polyimide during the blending process and achieve end capping at the end of the polyimide molecular chain in a covalent manner, thereby stably anchoring it in the polyimide network and effectively improving the compatibility between the two phases. At the same time, the heptyl chain grafted on its outside is a relatively long alkyl chain and belongs to a typical low surface energy chemical group. It can form a hydrophobic layer on the material surface, reduce the interaction force between it and water molecules, and enhance the overall hydrophobic performance of the material.
[0018] (2) The diamine monomer HFBAPP and the dianhydride monomer 6FDA used in this invention both contain -CF3 groups and flexible ether segments in their molecular structures. The polyimide molecular chains synthesized using these monomers are grafted with a large number of low surface energy -CF3 groups. At the same time, the ether chains, due to their inherent flexibility, effectively enhance the mobility of the polyimide molecular chains and expand the free volume of the chain segments, thereby providing the necessary kinetic conditions for the migration and enrichment of -CF3 groups to the surface during film formation. The synergistic effect of the above two structural features promotes the formation of a stable hydrophobic layer rich in -CF3 groups on the material surface, reduces the surface energy, and improves the overall hydrophobic properties of the polyimide film.
[0019] (3) This invention uses the surface of a lotus leaf as a template. First, polydimethylsiloxane (PDMS) is leveled and cured on its surface to create a negative template with a lotus leaf-like micro / nano structure. Then, a polyimide solution is coated onto the substrate and cured by heating. The micro / nano structure is accurately transferred to the polyimide surface using this negative template, thereby endowing the material with stable biomimetic superhydrophobic properties. This method has the advantages of simple process, high structural reproduction accuracy, and wide applicability. It can effectively simulate and controllably construct superhydrophobic structures in nature. The obtained micro / nano composite structure can effectively capture and trap air, forming a continuous and stable air cushion layer on the solid surface, significantly reducing the solid-liquid contact area, making the droplets approximately spherical and easy to roll off, thus endowing the material with superhydrophobic properties and self-cleaning ability, showing good application prospects in the fields of antifouling, anti-icing, and microfluidic transport. Attached Figure Description
[0020] Figure 1 This is the synthetic route for polyimide;
[0021] Figure 2 This is a schematic diagram illustrating the principle of superhydrophobicity.
[0022] Figure 3 The water contact angle of superhydrophobic shape memory polyimide. Detailed Implementation
[0023] The technical solution of the present invention will be further described below with reference to the accompanying drawings, but it is not limited thereto. Any modifications or equivalent substitutions to the technical solution of the present invention that do not depart from the spirit and scope of the technical solution of the present invention should be covered within the protection scope of the present invention.
[0024] The polyimide material provided by this invention is a fluorinated polyimide capped with cage-like silsesquioxane (POSS). Its main structure is copolymerized from 4,4'-(hexafluoroisopropene)phthalic anhydride (6FDA) and 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane (HFBAPP) in a molar ratio of 1.05:1. The amount of dianhydride used is slightly higher than that of diamine, which aims to make the polymer molecular chain ends mainly composed of anhydride groups, thereby providing active sites for the subsequent POSS capping reaction. The aminopropylheptyl cage-like silsesquioxane (NH2-POSS) used is a functionalized nanoparticle. The heptyl chain in its structure can endow the material with low surface energy characteristics, which helps to improve the hydrophobic properties of the material. At the same time, the amino group contained in the POSS molecule can be covalently bonded to the anhydride group at the end of the polyimide chain, realizing site-specific grafting and end-capping at the end of the molecular chain, thereby stably anchoring the POSS structural unit to the polymer chain, and further regulating the interfacial properties and aggregate structure of the material.
[0025] For the construction of surface structures, this invention provides a self-made polymer template method. Polydimethylsiloxane (PDMS) can be cured at low temperatures or even room temperature by adding a curing agent, and the cured substrate can be used at high temperatures of 200°C. Based on this characteristic, the fluid dynamic PDMS with added curing agent is poured onto the surface of a lotus leaf, covering the microstructure of the lotus leaf surface. After heating and curing, the PDMS substrate can accurately replicate the micro-nano structure of the lotus leaf surface, effectively transferring the surface structure of the lotus leaf precisely to the PDMS substrate that can be used for polyimide molding. The polyimide solution is poured onto the self-made template for molding, and after heating and curing, a biomimetic superhydrophobic polyimide material is obtained. Its surface has the same micro-nano structure as the lotus leaf surface. When water falls on its surface, an air cushion layer is left between the rough structure of the surface and the water interface, which can effectively reduce the contact area between the solid and liquid, reduce the water contact angle of the material surface, and endow the material with superhydrophobic properties.
[0026] A method for preparing a superhydrophobic polyimide material with shape memory function, such as Figure 1 As shown, the method includes the following steps:
[0027] Step S1: Mix PDMS elastomer matrix and curing agent in a weight ratio of 10:1 to obtain PDMS prepolymer; fix a fresh lotus leaf with veins removed at the bottom of the molding mold, pour the PDMS prepolymer into the mold, and place it in an oven at 60~80℃ for 3~5 hours to cure; after curing, separate the PDMS from the mold and use it as a biomimetic template.
[0028] Step S2: Dissolve HFBAPP in DMAc solvent, add 6FDA to HFBAPP solution in 4 to 6 portions, react at room temperature under N2 atmosphere for 20 to 30 h to obtain polyamic acid solution, named PAA. The solid content of the polyamic acid solution is 10 to 30 wt%, and the molar ratio of diamine to dianhydride is 1:1.05.
[0029] Step S3: Pour PAA onto a glass plate and place it in a vacuum oven for vacuum drying to remove air bubbles, resulting in PAA that is free of air bubbles after curing. The vacuum drying process is as follows: heat to 40~60℃ and hold for 1~3 hours, then heat to 80~100℃ and hold for 1~3 hours.
[0030] Step S4: Place the cured PAA without bubbles in a high-temperature oven and perform thermal imidization by gradient heating to obtain a polyimide (PI) film. The gradient heating process is as follows: heat to 110-130℃ at a heating rate of 1-5℃ / min and hold for 1-3 hours; heat to 150-170℃ at a heating rate of 1-5℃ / min and hold for 1-3 hours; heat to 190-210℃ at a heating rate of 1-5℃ / min and hold for 1-3 hours; heat to 240-260℃ at a heating rate of 1-5℃ / min and hold for 1-3 hours; heat to 290-310℃ at a heating rate of 1-5℃ / min and hold for 1-3 hours.
[0031] Step S5: Cut the PI film into small pieces and add it to DMAc solvent. Under N2 atmosphere, stir for 10-15 hours until dissolved. Add NH2-POSS to the solution and react at room temperature for 10-15 hours under N2 atmosphere to obtain a POSS-terminated PI solution, named POSS-PI. The amount of NH2-POSS added is 2-10 wt%. The PI film is dissolved in DMAc with a solid content of 5-15 wt%.
[0032] Step S6: Pour the POSS-PI solution onto the PDMS template, place a weight on top, and then place it in a vacuum oven at 80~100℃ for 1~3 hours. After removing air bubbles, the material is cured and demolded to obtain a shape memory polyimide material with biomimetic superhydrophobic function.
[0033] The shape memory function of shape memory polyimide is based primarily on the microstructure design of its molecular chains and reversible phase transition behavior. The material intelligently recovers its shape from a temporary to a permanent form through external stimulation. The material uses rigid imide segments as the stationary phase, forming a stable network structure through chemical cross-linking and physical interactions, thus fixing the permanent shape. Simultaneously, flexible segments or dynamic covalent bonds are introduced as the soft phase, endowing the material with the ability to move segments under specific conditions. In the shape memory cycle, when the material is heated to the soft phase activation temperature, the segment movement is enhanced, and the material enters a highly elastic state, allowing it to deform into a temporary shape under external force. Subsequently, when cooled below the glass transition temperature, the segment movement is frozen, and the temporary shape is fixed through the orientation and freezing of the molecular chains. When external stimulation is applied again, the soft phase segments are reactivated. Driven by the entropic elastic restoring force of the hard phase network, the molecular chains tend to return to the initial conformation, thus macroscopically restoring the material to its original permanent shape. This process essentially relies on the synergistic effect of the hard and soft phases in the polymer network. The hard phase provides the driving force and stability for shape recovery, while the soft phase achieves shape programming and fixation through reversible phase transitions. Overall, it reflects the intelligent response characteristics of polymer materials achieved through thermodynamic equilibrium and kinetic control.
[0034] Superhydrophobic Function Principle: Current explanations of superhydrophobic surfaces are mainly based on the Cassie-Baxter model: when a droplet is on a material surface, the liquid does not completely wet the rough surface; air remains underneath. Air exists between the solid and liquid phases, forming solid-liquid, solid-gas, and gas-liquid composite interfaces, reducing the solid-liquid contact area and thus lowering the water contact angle. In this invention, the superhydrophobicity of the material originates from the synergistic effect of the micro / nano-hierarchical structure mimicking a lotus leaf surface and low surface energy chemical modification. When a droplet is placed on the micro / nano-hierarchical surface, it cannot completely wet the grooves; some areas trap air, forming an "air cushion," resulting in the actual solid-liquid contact area being much smaller than the apparent geometric area. Due to the formation of the air cushion layer, the solid-liquid contact area is reduced, causing the droplet to roll off in a spherical shape. The superhydrophobic function principle diagram is shown below. Figure 2 As shown.
[0035] This invention relates to a shape-memory polyimide material based on biomimetic principles. By combining superhydrophobic properties with shape memory functionality, it exhibits significant advantages in extreme environment protection. This material effectively blocks liquid water penetration and possesses self-cleaning capabilities, making it suitable for cutting-edge technology fields such as outdoor electronic device protection, aerospace anti-icing, and microfluidic chips. For example, in the application of sensor protective covers for aerospace vehicles, this material not only effectively inhibits ice buildup and contaminant adhesion due to its superhydrophobic surface, but also, triggered by external temperature fluctuations, utilizes the shape memory effect to drive controlled deformation of the material, thereby actively peeling off existing thin ice and achieving intelligent synergy between anti-icing and surface self-cleaning functions.
[0036] Comparative Example 1
[0037] (1) PDMS prepolymer is obtained by mixing PDMS elastomer matrix and curing agent at a weight ratio of 10:1; a fresh leaf with veins removed is fixed at the bottom of the molding mold, the PDMS prepolymer is poured into the mold, and it is placed in an oven at 60°C for 4 hours; after curing, the PDMS is separated from the mold and used as a biomimetic template.
[0038] (2) Dissolve 1.8870 g HFBAPP in 17.5 mL DMAc solvent, add 1.6980 g 6FDA to the diamine solution in 4 to 6 portions, under N2 atmosphere, stirring at 250 r / min, react at room temperature for 24 h to obtain a polyamic acid solution with a solute content of 20 wt%, named PAA;
[0039] (3) Spread PAA evenly on a glass plate and place it in a vacuum oven for vacuum drying: heat up to 50°C and keep warm for 2 hours, then heat up to 80°C and keep warm for 2 hours to obtain PAA that is free of bubbles after curing.
[0040] (4) The cured PAA without bubbles was placed in a high-temperature oven and thermal imidized by gradient heating: heating to 120℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 160℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 200℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 250℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 300℃ at a heating rate of 1℃ / min and holding for 2 h to obtain polyimide (PI) film.
[0041] (5) Take 1 g of PI film, cut it into small pieces, add it to 10.0 mL of DMAc solvent, stir for 12 h under N2 atmosphere until dissolved;
[0042] (6) Spread the PI solution evenly on the PDMS template, place a weight on top, and keep it in a vacuum oven at 80°C for 2 hours. After removing the air bubbles, solidify and demold to obtain a shape memory polyimide material with biomimetic superhydrophobic function.
[0043] Example 1
[0044] (1) PDMS prepolymer is obtained by mixing PDMS elastomer matrix and curing agent at a weight ratio of 10:1; a fresh leaf with veins removed is fixed at the bottom of the molding mold, the PDMS prepolymer is poured into the mold, and it is placed in an oven at 60°C for 4 hours; after curing, the PDMS is separated from the mold and used as a biomimetic template.
[0045] (2) Dissolve 1.8870 g HFBAPP in 17.5 mL DMAc solvent, add 1.6980 g 6FDA to the diamine solution in 4 to 6 portions, under N2 atmosphere, stirring at 250 r / min, react at room temperature for 24 h to obtain a polyamic acid solution with a solute content of 20 wt%, named PAA;
[0046] (3) Spread PAA evenly on a glass plate and place it in a vacuum oven for vacuum drying: heat up to 50°C and keep warm for 2 hours, then heat up to 80°C and keep warm for 2 hours to obtain PAA that is free of bubbles after curing.
[0047] (4) The cured PAA without bubbles was placed in a high-temperature oven and thermal imidized by gradient heating: heating to 120℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 160℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 200℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 250℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 300℃ at a heating rate of 1℃ / min and holding for 2 h to obtain polyimide (PI) film.
[0048] (5) Take 1 g of PI film, cut it into pieces and add it to 10.0 mL of DMAc solvent. Stir for 12 h under N2 atmosphere until dissolved. Add 0.0100 g of NH2-POSS to the above solution. React at room temperature under N2 atmosphere for 12 h to obtain a 2% POSS-terminated PI solution, named POSS-PI.
[0049] (6) Spread the POSS-PI solution evenly on the PDMS template, place a weight on top, and then place it in a vacuum oven at 80°C for 2 hours. After removing the air bubbles, the material is cured and demolded to obtain a shape memory polyimide material with biomimetic superhydrophobic function.
[0050] Example 2
[0051] (1) PDMS prepolymer is obtained by mixing PDMS elastomer matrix and curing agent at a weight ratio of 10:1; a fresh leaf with veins removed is fixed at the bottom of the molding mold, the PDMS prepolymer is poured into the mold, and it is placed in an oven at 60°C for 4 hours; after curing, the PDMS is separated from the mold and used as a biomimetic template.
[0052] (2) Dissolve 1.8870 g HFBAPP in 17.5 mL DMAc solvent, add 1.6980 g 6FDA to the diamine solution in 4 to 6 portions, under N2 atmosphere, stirring at 250 r / min, react at room temperature for 24 h to obtain a polyamic acid solution with a solute content of 20 wt%, named PAA;
[0053] (3) Spread PAA evenly on a glass plate and place it in a vacuum oven for vacuum drying: heat up to 50°C and keep warm for 2 hours, then heat up to 80°C and keep warm for 2 hours to obtain PAA that is free of bubbles after curing.
[0054] (4) The cured PAA without bubbles was placed in a high-temperature oven and thermal imidized by gradient heating: heating to 120℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 160℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 200℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 250℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 300℃ at a heating rate of 1℃ / min and holding for 2 h to obtain polyimide (PI) film.
[0055] (5) Take 1 g of PI film, cut it into pieces and add it to 10.0 mL of DMAc solvent. Stir for 12 h under N2 atmosphere until dissolved. Add 0.0200 g of NH2-POSS to the above solution. React at room temperature under N2 atmosphere for 12 h to obtain a 4% POSS-terminated PI solution, named POSS-PI.
[0056] (6) Spread the POSS-PI solution evenly on the PDMS template, place a weight on top, and then place it in a vacuum oven at 80°C for 2 hours. After removing the air bubbles, the material is cured and demolded to obtain a shape memory polyimide material with biomimetic superhydrophobic function.
[0057] Example 3
[0058] (1) PDMS prepolymer is obtained by mixing PDMS elastomer matrix and curing agent at a weight ratio of 10:1; a fresh leaf with veins removed is fixed at the bottom of the molding mold, the PDMS prepolymer is poured into the mold, and it is placed in an oven at 60°C for 4 hours; after curing, the PDMS is separated from the mold and used as a biomimetic template.
[0059] (2) Dissolve 1.8870 g HFBAPP in 17.5 mL DMAc solvent, add 1.6980 g 6FDA to the diamine solution in 4 to 6 portions, under N2 atmosphere, stirring at 250 r / min, react at room temperature for 24 h to obtain a polyamic acid solution with a solute content of 20 wt%, named PAA;
[0060] (3) Spread PAA evenly on a glass plate and place it in a vacuum oven for vacuum drying: heat up to 50°C and keep warm for 2 hours, then heat up to 80°C and keep warm for 2 hours to obtain PAA that is free of bubbles after curing.
[0061] (4) The cured PAA without bubbles was placed in a high-temperature oven and thermal imidized by gradient heating: heating to 120℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 160℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 200℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 250℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 300℃ at a heating rate of 1℃ / min and holding for 2 h to obtain polyimide (PI) film.
[0062] (5) Take 1 g of PI film, cut it into pieces and add it to 10.0 mL of DMAc solvent. Stir for 12 h under N2 atmosphere until dissolved. Add 0.0300 g of NH2-POSS to the above solution. React at room temperature for 12 h under N2 atmosphere to obtain a 6% POSS-terminated PI solution, named POSS-PI.
[0063] (6) Spread the POSS-PI solution evenly on the PDMS template, place a weight on top, and then place it in a vacuum oven at 80°C for 2 hours. After removing the air bubbles, the material is cured and demolded to obtain a shape memory polyimide material with biomimetic superhydrophobic function.
[0064] Example 4
[0065] (1) PDMS prepolymer is obtained by mixing PDMS elastomer matrix and curing agent at a weight ratio of 10:1; a fresh leaf with veins removed is fixed at the bottom of the molding mold, the PDMS prepolymer is poured into the mold, and it is placed in an oven at 60°C for 4 hours; after curing, the PDMS is separated from the mold and used as a biomimetic template.
[0066] (2) Dissolve 1.8870 g HFBAPP in 17.5 mL DMAc solvent, add 1.6980 g 6FDA to the diamine solution in 4 to 6 portions, under N2 atmosphere, stirring at 250 r / min, react at room temperature for 24 h to obtain a polyamic acid solution with a solute content of 20 wt%, named PAA;
[0067] (3) Spread PAA evenly on a glass plate and place it in a vacuum oven for vacuum drying: heat up to 50°C and keep warm for 2 hours, then heat up to 80°C and keep warm for 2 hours to obtain PAA that is free of bubbles after curing.
[0068] (4) The cured PAA without bubbles was placed in a high-temperature oven and thermal imidized by gradient heating: heating to 120℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 160℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 200℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 250℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 300℃ at a heating rate of 1℃ / min and holding for 2 h to obtain polyimide (PI) film.
[0069] (5) Take 1 g of PI film, cut it into pieces and add it to 10.0 mL of DMAc solvent. Stir for 12 h under N2 atmosphere until dissolved. Add 0.0400 g of NH2-POSS to the above solution. React at room temperature for 12 h under N2 atmosphere to obtain a PI solution with a concentration of 8% POSS-terminated, named POSS-PI.
[0070] (6) Spread the POSS-PI solution evenly on the PDMS template, place a weight on top, and then place it in a vacuum oven at 80°C for 2 hours. After removing the air bubbles, the material is cured and demolded to obtain a shape memory polyimide material with biomimetic superhydrophobic function.
[0071] Example 5
[0072] (1) PDMS prepolymer is obtained by mixing PDMS elastomer matrix and curing agent at a weight ratio of 10:1; a fresh leaf with veins removed is fixed at the bottom of the molding mold, the PDMS prepolymer is poured into the mold, and it is placed in an oven at 60°C for 4 hours; after curing, the PDMS is separated from the mold and used as a biomimetic template.
[0073] (2) Dissolve 1.8870 g HFBAPP in 17.5 mL DMAc solvent, add 1.6980 g 6FDA to the diamine solution in 4 to 6 portions, under N2 atmosphere, stirring at 250 r / min, react at room temperature for 24 h to obtain a polyamic acid solution with a solute content of 20 wt%, named PAA;
[0074] (3) Spread PAA evenly on a glass plate and place it in a vacuum oven for vacuum drying: heat up to 50°C and keep warm for 2 hours, then heat up to 80°C and keep warm for 2 hours to obtain PAA that is free of bubbles after curing.
[0075] (4) The cured PAA without bubbles was placed in a high-temperature oven and thermal imidized by gradient heating: heating to 120℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 160℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 200℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 250℃ at a heating rate of 1℃ / min and holding for 2 h; heating to 300℃ at a heating rate of 1℃ / min and holding for 2 h to obtain polyimide (PI) film.
[0076] (5) Take 1 g of PI film, cut it into pieces and add it to 10.0 mL of DMAc solvent. Stir for 12 h under N2 atmosphere until dissolved. Add 0.0500 g of NH2-POSS to the above solution. React at room temperature under N2 atmosphere for 12 h to obtain a 10% POSS-terminated PI solution, named POSS-PI.
[0077] (6) Spread the POSS-PI solution evenly on the PDMS template, place a weight on top, and then place it in a vacuum oven at 80°C for 2 hours. After removing the air bubbles, the material is cured and demolded to obtain a shape memory polyimide material with biomimetic superhydrophobic function.
[0078] The water contact angle of the superhydrophobic shape memory polyimide material was tested using a JY-PHB contact angle analyzer. The test results are as follows: Figure 3 As shown in Table 1.
[0079] Table 1
[0080]
Claims
1. A biomimetic superhydrophobic shape memory polyimide material, characterized in that... The shape memory polyimide material is a fluorinated polyimide with cage-like silsesquioxane end caps. The main structure is copolymerized from 4,4'-(hexafluoroisopropene)phthalic anhydride 6FDA and 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane HFBAPP in a molar ratio of 1.05:
1.
2. A method for preparing the biomimetic superhydrophobic shape memory polyimide material according to claim 1, characterized in that... The method includes the following: Step S1: Mix the PDMS elastomer matrix and curing agent to obtain the PDMS prepolymer; fix a fresh lotus leaf with veins removed at the bottom of the molding mold, pour the PDMS prepolymer into the mold, and place it in an oven to cure. After curing, the PDMS is separated from the mold and used as a biomimetic template; Step S2: Dissolve HFBAPP in DMAc solvent, add 6FDA to the HFBAPP solution in 4 to 6 portions, react at room temperature under N2 atmosphere for 20 to 30 h to obtain polyamic acid solution, named PAA. Step S3: Pour PAA onto a glass plate and place it in a vacuum oven for vacuum drying to remove air bubbles, resulting in PAA that is free of air bubbles after curing. Step S4: Place the cured PAA without bubbles in a high-temperature oven and perform thermal imidization by gradient heating to obtain a polyimide PI film. Step S5: Cut the PI film into small pieces and add it to DMAc solvent. Stir until dissolved under N2 atmosphere. Add NH2-POSS to the solution and react at room temperature for 10-15 hours under N2 atmosphere to obtain a POSS-terminated PI solution, named POSS-PI. Step S6: Pour the POSS-PI solution onto the PDMS template, place it in a vacuum oven at 80~100℃ for 1~3 hours, remove air bubbles, cure, demold, and obtain a shape memory polyimide material with biomimetic superhydrophobic function.
3. The method for preparing the biomimetic superhydrophobic shape memory polyimide material according to claim 2, characterized in that... In step S1, the weight ratio of PDMS elastomer matrix to curing agent is 10:1, the curing temperature is 60~80℃, and the curing time is 3~5 hours.
4. The method for preparing the biomimetic superhydrophobic shape memory polyimide material according to claim 2, characterized in that... In step S2, the solid content of the polyamic acid solution is 10~30wt%.
5. The method for preparing the biomimetic superhydrophobic shape memory polyimide material according to claim 2, characterized in that... In step S3, the vacuum drying process is as follows: heat up to 40~60℃, keep warm for 1~3 hours, heat up to 80~100℃, keep warm for 1~3 hours.
6. The method for preparing the biomimetic superhydrophobic shape memory polyimide material according to claim 2, characterized in that... In step S4, the gradient heating process is as follows: heating to 110-130℃ at a heating rate of 1-5℃ / min, holding for 1-3 hours; heating to 150-170℃ at a heating rate of 1-5℃ / min, holding for 1-3 hours; heating to 190-210℃ at a heating rate of 1-5℃ / min, holding for 1-3 hours; heating to 240-260℃ at a heating rate of 1-5℃ / min, holding for 1-3 hours; and heating to 290-310℃ at a heating rate of 1-5℃ / min, holding for 1-3 hours.
7. The method for preparing the biomimetic superhydrophobic shape memory polyimide material according to claim 2, characterized in that... In step S5, the concentration of NH2-POSS in the POSS-terminated PI solution is 2~10wt%.
8. The method for preparing the biomimetic superhydrophobic shape memory polyimide material according to claim 2, characterized in that... In step S5, the PI film is dissolved in DMAc, with a solid content of 5~15wt%.